PERAN AISIYIYAH MUHAMMADIYAH DALAM KEBERHASILAN PEMBINAAN PENDIDIKAN AGAMA DI ERA DIGITAL: Analysis of the contribution of Mrs. Aisiyiyah Muhammadiyah and the challenges of developing digital-based religious education - adyani, wali_atmamil; Layyinnati, Idzi’ (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
The role of Aisiyiyah Muhammadiyah in the succes of religious education development in the succes of religious education development in the digital era is signitificant in addressing the challenges of globalization and technological advancements.This study aims to analyze the countributions of Aisiyiyah Muhammadiyah in enhancing the quality of religious education through the utilizationof digital technology. The research employs a qualitative method with a descriptive-analytical approach. Data were colloected thourgh interviews, observations, and document analysis related to Aisiyiyah Muhammadiyah’s programs. The finding reveal that Aisiyiyah Muhammadiyah actively coutributes to religious education development by developing digital platfrom. Keyword: Aisiyiyah Muhammadiyah, religious education, digital era.